Not on my watch: understanding the affordances of self-tracking for adolescents' social and psychological wellbeing - Freeman, JL (2023)
We can see aspects of our everyday lives through data – how many steps we took to the supermarket, how many kilometres we covered walking the dog, or how many calories we burned cycling to work. Whilst self-tracking is not new, and indeed not always digital, we have seen the continuing development of digital tools that enable us to monitor, control, and analyse vast quantities of personal health data. Self-tracking tools have become increasingly relevant in the wake of the COVID-19 pandemic. COVID-19 has raised important questions about what it means to track data, what it means to be tracked, and how we understand the consequences of tracked data. Never has it been more apparent that our self-tracked data have social consequences.